The gendering of coaching from an athlete perspective: The case of Norwegian boxing - Hovden, J.; Tjønndal, A. (International Review for the Sociology of Sport, 2019)
Coaching is a male dominated area of sport. Globally, women coaches represent a small minority and only a few women coach male athletes. In Norway it is estimated that only about 19% of all coaches are women. In this article we engage in issues regarding the gendering of coaching from an athlete perspective. The concerns are how meanings of gender mirror the athletes` perceptions and experiences of coaching practices. The theoretical framework develops our understanding of gender and how leadership ideals and practices are structured by and through gender. The data material consists of qualitative interviews with Norwegian boxers. The analysis demonstrates that male coaches earn the respect of their boxers more easily than female coaches do. Furthermore, female boxers experience a more open and socially supportive coach-athlete relationship with female coaches. The coach-athlete relationship with male coaches is often shaped by paternalism, which particularly seems to represent a challenge for young female athletes. The interviewees describe sound coaching as consisting of leadership forms associated with both masculine and feminine skills.